Malaria rapid diagnostic test performance : results of WHO product testing of malaria RDTs : round ... [2009- ]- (WHO GenevaCH, 2010)
Presents an overview of the results of the first, second and third rounds of WHO product testing of malaria antigen-detecting RDTs (Rapid Diagnostic Tests) completed in 2008, 2009 and 2011 respectively, published in conjunction with the release of the results of Round 2 and 3.
Documentation Centre has: 2009; 2010-2011; 2012